Coração Partido: o luto pela perda do cônjuge - Prizanteli, Cristiane Corsini (2008)
Loss resulting from death is a critical situation, and the death of a spouse often represents one of the greatest losses in life. There is an increased risk of mortality among patients in grief, when compared to those not thrown into mourning, besides an increased use of health services. There have been investigations on individual and/or situational variables which might explain why a significant proportion of people in grief resulting from the death of a spouse have their health affected. Stress seems to be associated to a kind of cardiopathy called Broken Heart Syndrome. Such Syndrome may be considered as metaphor, which take place immediately after a severe physical or psychological stressful episode, to which an individual responds much the same way as to a heart attack. The aim of the present study was to figure out how mourning affected widowhood with presentation cardiac symptoms without physical causes. The study was conducted one year and five months after the death of her spouse. Our results indicated that the widow sustained severe psychological pain, which triggered the cardiac symptoms characterized as the Broken Heart Syndrome. Such severe psychological suffering leads to chest pain that is similar to a heart attack. The subject reported that her health care professionals did not sympathize with her psychological suffering. Furthermore, it was clear that the loss brought about consequences that can be seem in the whole family